Optimized Distortion in Linear Social Choice - Ge, Luise; Kehne, Gregory; Vorobeychik, Yevgeniy (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Social choice theory offers a wealth of approaches for selecting a candidate on behalf of voters based on their reported preference rankings over options. When voters have explicit utilities for these options, however, using preference rankings may lead to suboptimal outcomes vis-a-vis utilitarian social welfare. Distortion is a measure of this suboptimality, and an extensive literature uses it to develop and analyze voting rules when utilities have minimal structure. However, in many settings, such as common paradigms for value alignment, available options admit a vector representation, and it is natural to suppose that utilities are parametric functions thereof.We undertake the first study of distortion for linear utility functions. Our theoretical contributions are organized into two parts: randomized and deterministic voting rules. We obtain bounds that depend only on dimension of the candidate embedding, and are independent of the numbers of candidates or voters. Additionally, we introduce poly-time instance-optimal algorithms for minimizing distortion given a collection of candidates and votes. We empirically evaluate these in two real-world domains: recommendation systems using collaborative filtering embeddings, and opinion surveys utilizing language model embeddings. Our results benchmark the distortion bounds of several standard rules against our instance-optimal algorithms.